Jurisdiction and applicable law to contracts for the sale of goods and the provision of services including the carriage of goods by sea and other means of transport in the European Union - Echebarría Fernández, Jonatan (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The article analyses the jurisdiction and applicable law to contracts for the sale of godos and the provision of services in the European Union. It particularly focuses on contracts that subsume different categories of contracts, such as the carriage of goods by sea, in a contract for the sale of godos and the provision of services. The European Union law and the interpretation provided by the Court of Justice of the European Union shed light into the place of performance of the contract in order to set jurisdiction for national courts. This is explained through the current legal framework and the case law in order to ascertain where and under what legal regime the claimant may start proceedings for the breach of a contractual obligation or in case of a non-contractual claim.